La casa como espacio violento: develando salidas a partir de la teologia feminista - Hilario, Irene Ricardina Ponce (2006)
This research is born out of my personal experience of violence and also out of my personal observation of daily life and pastoral work in a poor neighborhood in Lima. I will employ the phenomenological method in order to retrieve my history from memories about my relationship at home. This method attempts to value women history and also to retrieve it out of a wider dynamic that englobes the relationship between women and men and between women and other women. I will, then, try to make an epistemological analysis of violence, in order to understand the social process of violence. The focus of the analysis will be the concept of gender. In the first moment I will analize the relationship between agressor and victim, then the focus is on the aggressor. I will try to undestand the role of gender to uncovering the patriarcal axis that rules the social fabric. In order to do that, will be necessary to focus also on the agressor as a product of the social system. This approach to the male identify construction offers some clues to understand the mechanism that leads into the perpetuation of male supremacy , which, on other hand, prevents just and equal reationships between men and women from taking place. The paradoxal and the challenging elements in this work are the view of the agressor as a victim of the patriarchal ideology and the search for a way of reconciliation between agressor and victim based on biblical claim of forgiveness, once the justice has not solved the problem through the sanctions enforcement. I do not intend to justify the agressor way, but to offer elements that help to build a proposal for violence preventing. The third chapter focus on the role of men in church, in order to design a pastoral plan theologically informed that plan as its major goal to help the church to develop pastoral work for violent men.